Isolation, Characterization, and Identification of Biological Control Agent for Potato Soft Rot in Bangladesh - M. M. Rahman; M. E. Ali; A. A. Khan; A. M. Akanda; Md. Kamal Uddin; U. Hashim; S. B. Abd Hamid (The Scientific World Journal)
A total of 91 isolates of probable antagonistic bacteria of potato soft rot bacterium Erwinia carotovora subsp. carotovora (Ecc) were extracted from rhizospheres and endophytes of various crop plants, different soil varieties, and atmospheres in the potato farming areas of Bangladesh. Antibacterial activity of the isolated probable antagonistic bacteria was tested in vitro against the previously identified most common and most virulent soft rot causing bacterial strain Ecc P-138. Only two isolates E-45 and E-65 significantly inhibited the in vitro growth of Ecc P-138. Physiological, biochemical, and carbon source utilization tests identified isolate E-65 as a member of the genus Bacillus and the isolate E-45 as Lactobacillus sp. The stronger antagonistic activity against Ecc P-138 was found in E-65 in vitro screening and storage potatoes. E-65 reduced the soft rot infection to 22-week storage potatoes of different varieties by 32.5–62.5% in model experiment, demonstrating its strong potential to be used as an effective biological control agent for the major pectolytic bacteria Ecc. The highest (62.5%) antagonistic effect of E-65 was observed in the Granola and the lowest (32.7%) of that was found in the Cardinal varieties of the Bangladeshi potatoes. The findings suggest that isolate E-65 could be exploited as a biocontrol agent for potato tubers.